2016
DOI: 10.1128/mbio.00252-16
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of Fungal Exopolysaccharide Mediates Adhesion and Biofilm Formation

Abstract: The mold Aspergillus fumigatus causes invasive infection in immunocompromised patients. Recently, galactosaminogalactan (GAG), an exopolysaccharide composed of galactose and N-acetylgalactosamine (GalNAc), was identified as a virulence factor required for biofilm formation. The molecular mechanisms underlying GAG biosynthesis and GAG-mediated biofilm formation were unknown. We identified a cluster of five coregulated genes that were dysregulated in GAG-deficient mutants and whose gene products share functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
200
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(226 citation statements)
references
References 54 publications
3
200
0
Order By: Relevance
“…Our recent work on Aspergillus has identified a cluster of five genes that encode the proteins necessary for GAG biosynthesis (15). As with P. aeruginosa, we found that the product of one of these genes contains a glycoside hydrolase domain, Sph3 h , which is capable of hydrolyzing purified and cell wall-associated GAG (23).…”
Section: Significancementioning
confidence: 88%
See 2 more Smart Citations
“…Our recent work on Aspergillus has identified a cluster of five genes that encode the proteins necessary for GAG biosynthesis (15). As with P. aeruginosa, we found that the product of one of these genes contains a glycoside hydrolase domain, Sph3 h , which is capable of hydrolyzing purified and cell wall-associated GAG (23).…”
Section: Significancementioning
confidence: 88%
“…For fungal burden analysis, lungs were homogenized in 5 mL of PBS containing protease inhibitor mixture (Roche), and aliquots were stored at −80°C until use. Pulmonary fungal burden was determined as described (15), and as detailed in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAG is an ␣-1,4-linked heteropolysaccharide composed of galactose and partially deacetylated GalNAc that is absent in A. fumigatus spores but is produced in abundance by growing hyphae (8,11,14). GAG plays a critical role in the maintenance of the extracellular matrix of A. fumigatus biofilms (8).…”
Section: A Fumigatus Biofilm Exopolysaccharidesmentioning
confidence: 99%
“…GAG is a partially deacetylated heteropolymer of ␣-1,4-linked galactose and N-acetyl galactosamine, which mediates adhesion between both fungi and also to other surfaces as well as protection against host immune defenses (8 -11). GAG is synthesized by the protein products of a conserved cluster of five genes that is present in a number of plant and human fungal pathogens (11). Despite a lack of sequence homology with bacterial exopolysaccharide biosynthetic enzymes, there are striking similarities in the function and organization of these fungal exopolysaccharide biosynthetic proteins and the role of the resulting glycans in biofilm formation, drug resistance, and immune evasion.…”
mentioning
confidence: 99%